Implementation of the Trusted Self Fisherman Insurance Program (Simantep) In Sibolga City - Melisa Octafany; R Hamdani Harahap; Bengkel Ginting (Budapest International Research and Critics University, 2022)
As an effort to increase food sovereignty, the Government requires protection and welfare for the main actors of food security, one of which is fishermen. The government protects fishermen through the SiMantep independent fishermen insurance program (Trusted Independent Fishermen Insurance). The SiMantep self-insurance program is a continuation of the Fisherman Insurance Premium Assistance (BPAN) program from the Ministry of Maritime Affairs and Fisheries (KKP) which was provided in 2016 and 2017. The purpose of this study was to analyze the implementation of the Trusted Independent Fishermen Insurance Program (Simantep) policy in Sibolga City, and the supporting and inhibiting factors for its implementation. This type of descriptive qualitative research. Methods of collecting data were observation, interviews and documentation. The results of the research. Implementation of the Trusted Independent Fishermen Insurance Program (Simantep) of the Fisheries, Food Security, and Agriculture (PKPP) Sibolga City has been running in accordance with the Regulation of the Director General of Capture Fisheries Number 3 of 2018 concerning Technical Instructions for Trusted Independent Fishermen Insurance (Simantep), but still there are several problems in its implementation, there is information that is not clear, not comprehensive, and the fisherman's thinking ability is still lacking which results in delays in program socialization. According to George Edwards there are four indicators of implementation, among others: Communication factors. The Fisheries Insurance Service for Fishermen has coordinated with PT Jasindo to socialize the implementation of the program to fishermen. Factors Resources, especially the staff they have are still lacking. So that data collection and verification of fishermen is fairly slow. The disposition factor/attitude of the implementers welcomed the policy of guaranteeing protection against the risk of work accidents for fishermen according to the Standard Operating Procedures (SOP) of the KKP technical guidelines. The inhibiting factor in implementation is the lack of participation of fishermen in understanding the importance of guaranteeing protection against the risk of accidents and secondly the lack of staff implementing policies for the guarantee program for protection against the risk of work accidents for fishermen.